GAGASAN REVOLUSI PEMBELAJARAN NABI MUHAMMAD SAW: RELEVANSINYA TERHADAP BASIS HUMANISME-RELIGIUS KONSEP PEMBELAJARAN ABAD 21 - Saidina Ali; Nijo; Abdul Wahab (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to find out the Learning Revolution ala Prophet Muhammad Saw: Reflectively, this review wants to revisit the substance of the Learning Revolution ala Prophet Muhammad Saw as a Conceptual Footing of Humanism-Religion-Based Learning in the 21st Century. Reviewing methods, rhetoric, the way the prophet presents, and personality as a teacher in teaching as a Conceptual Footing of Humanism-Religion-Based Learning in the 21st Century. The method used is the literature method. Based on the results of the study, it can be concluded that there are findings about the Learning Revolution in the style of the Prophet Muhammad Saw as a Conceptual Footing for Humanism-Religion-Based Learning in the 21st Century. Methods, rhetoric, presentation methods, and personality as a teacher in teaching in the style of the Prophet Muhammad SAW are still relevant to PAI learning in the 21st century.